Anterior Cruciate Ligament Injury and its Rehabilitation in Nepal - Suraj Bhusal (Journal of Nepal Medical Association, 2021)
Anterior cruciate ligament is one of the most common ligaments to get injured especially in athletic population. It is a band of dense connective tissue which arises from the antero-medial aspect of the inter condylar area on the tibial plateau and passes upwards and backwards to attach to the posteromedial aspect of the lateral femoral condyle. There is increasing rate of its reported injuries among athletes in Nepal and surgeons report increased consultations among athletes regarding adequate intervention strategies. Factors like over use, inadequate recovery time, playing surface, fitness incompatibility are involved in the increase of anterior cruciate ligament injury among athletes in Nepal. Treatment approach for anterior cruciate ligament injury is ever evolving with regular studies and innovation, but constant guidance and rehabilitation in an institution-based setting have shown positive feedback in recovery and return to play.